Adult aplastic anemia patients can maintain remission after allogeneic hematopoietic stem cell transplantation in a mixed chimeric state - Başcı, Semih; Yiğenoğlu, Tuğçe Nur; Bakırtaş, Mehmet; Uncu Ulu, Bahar; Şahin, Derya; Darçın, Tahir; Yıldız, Jale; İskender, Dicle and Baysal, Nuran Ahu and Dal, Sinan and Kızıl Çakır, Merih and Altuntaş, Fevzi (Journal of Surgery and Medicine, 2020)
Aim: Allogeneic stem cell transplantation (allo-SCT) is performed as a curative treatment in young, fit, severe aplastic anemia (SAA) and very severe aplastic anemia (VSAA) patients. Age is one of the most significant factors that impact survival after transplantation. With advancing age, survival rates decrease, therefore it is crucial to perform allo-SCT without any delay in appropriate SAA and VSAA patients. Mixed chimerism (MC) in the post-allo-SCT period may be a sign of relapse or graft failure. In this study, we aimed to evaluate the outcome of allo-SCT in adult SAA and VSAA patients and the significance of chimerism monitoring in follow up. Methods: The data of 16 adult AA patients who underwent allo-SCT at our center were included in this observational study. HLA match, conditioning regimens, chimerism and remission status were recorded. Results: Median PFS was 70.4 months and median OS was 89.7 months in all patients. During the follow-up period, 9 patients remained fully chimeric whereas 6 patients had MC. The chimerism level of one patient, who had engraftment failure, was <5%. Both fully chimeric and mixed chimeric patients remained in remission. Conclusion: More AA patients can be treated with allo-SCT with more optimized conditioning regimens that provide sustained engraftment with minimum toxicity. Our study showed that adult AA patients can maintain remission for a long time after allo-SCT, even in a mixed chimeric state.